2016
DOI: 10.1002/phar.1749
|View full text |Cite
|
Sign up to set email alerts
|

Bazedoxifene and Conjugated Equine Estrogen: A Combination Product for the Management of Vasomotor Symptoms and Osteoporosis Prevention Associated with Menopause

Abstract: Bazedoxifene (BZA), a third-generation selective estrogen receptor modulator (SERM), has been combined with conjugated equine estrogen (CE) to create a tissue selective estrogen complex (TSEC) for the management of vasomotor symptoms (VMS) and the prevention of osteoporosis (OP) associated with menopause. Both of these outcomes of menopause contribute to significant negative effects on quality of life and increases in utilization of health care resources and dollars. Current treatment modalities for VMS and OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…However, the use of bazedoxifene in subjects with hepatic impairment is not recommended. 22 Similar pharmacokinetic characteristics have been observed with other SERMs in patients with hepatic impairment. Raloxifene is metabolized primarily in the liver and intestines by glucuronidation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the use of bazedoxifene in subjects with hepatic impairment is not recommended. 22 Similar pharmacokinetic characteristics have been observed with other SERMs in patients with hepatic impairment. Raloxifene is metabolized primarily in the liver and intestines by glucuronidation.…”
Section: Discussionsupporting
confidence: 71%
“…In an unpublished, randomized, double‐blind, placebo‐controlled, and open‐label moxifloxacin‐controlled crossover study of the effects of bazedoxifene on QTc, a therapeutic dose of 20 mg and a supratherapeutic dose of 120 mg did not result in a clinically significant increase in QTc interval (defined as a 90% confidence interval upper bound of 10 milliseconds for baseline‐adjusted difference vs placebo) in healthy postmenopausal women (Pfizer, data on file). However, the use of bazedoxifene in subjects with hepatic impairment is not recommended …”
Section: Discussionmentioning
confidence: 99%
“…The approval of Duavee ® CE (0.45mg)/BZA(20mg) was based on Selective Estrogen, Menopause, and Response to Therapy (SMART) trials that aimed to evaluate CE/BZA's safety and efficacy in the management of moderate-to-severe vasomotor symptoms, bone mineral density, endometrial hyperplasia, moderate-to-severe vulvar/vaginal atrophy, and overall safety (Kagan et al, 2010, Umland et al, 2016. In parallel, preclinical studies in animal models reported beneficial effect on metabolic parameters (Barrera et al, 2014, Kim et al, 2014 and have shown that, when combined with CE, BZA attenuates CE-induced uterine and mammary gland cell proliferation (Kim et al, 2014, Barrera et al, 2014, Peano et al, 2009, Song et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been approved by the European Medicines Agency (EMA) (Komm and Mirkin, 2013). The efficacy and safety of CE+BZA in postmenopausal women, and the impact of this drug combination on quality of life was evaluated through a series of five pivotal phase 3 randomized, double-blinded, multicentered, active and/or placebo-controlled studies, called the Selective estrogens, Menopause And Response to Therapy (SMART) trials (Kagan et al, 2010, Umland et al, 2016. From these trials, CE+BZA was found to be associated with significant benefits such as a reduction in the frequency and severity of vasomotor symptoms, the prevention of bone loss, improved sleep and better menopausespecific quality of life, whilst also providing a reasonable level of protection against endometrial hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…WHO FRAX ( http:www.shef.ac.uk/FRAX ) 62 . Whereas bisphosphonates, denosumab and teriparatide are used for the treatment of patients with a full-blown osteoporosis, selective oestrogen receptor modulators may be considered as the first-line treatment in preventing bone loss in women within 10 years of the menopause, side by side with the menopausal hormonal therapy (MHT) and the most recent combination of bazedoxifene and oestrogen 63 .…”
Section: Anti-osteoporotic Therapies Targeting Oxidative Stress: Currmentioning
confidence: 99%